2005
DOI: 10.1097/01.olq.0000190057.61633.8d
|View full text |Cite
|
Sign up to set email alerts
|

Women Find It Easy and Prefer to Collect Their Own Vaginal Swabs to Diagnose Chlamydia trachomatis or Neisseria gonorrhoeae Infections

Abstract: Self-collected vaginal swabs were easy to collect and patients preferred them over urine and cervical swabs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 22 publications
7
107
1
1
Order By: Relevance
“…Many authors have advocated the use of self-taken vulvovaginal-swab specimens as suitable, acceptable, convenient, and effective in screening for C. trachomatis in a variety of clinical settings (5,25,26). Our study also showed that vulvovaginal-swab specimens collected at home and mailed to a laboratory are suitable diagnostic specimens for use with nucleic acid amplification tests.…”
Section: Discussionmentioning
confidence: 50%
“…Many authors have advocated the use of self-taken vulvovaginal-swab specimens as suitable, acceptable, convenient, and effective in screening for C. trachomatis in a variety of clinical settings (5,25,26). Our study also showed that vulvovaginal-swab specimens collected at home and mailed to a laboratory are suitable diagnostic specimens for use with nucleic acid amplification tests.…”
Section: Discussionmentioning
confidence: 50%
“…For women, the endocervical swab has been the standard sample for most tests approved by the U.S. Food and Drug Administration. Recently, however, the sensitivity for detection of chlamydial or gonococcal infection with vaginal swabs was shown to be similar to that with endocervical swabs (5,7,26). In the present study, endocervical swabs contained the highest C. trachomatis organism load (2231 EBs/100 l), followed by SCVSs (773 EBs/100 l), urethral swabs (162 EBs/100 l), and FVU specimens (47 EBs/100 l).…”
Section: Discussionmentioning
confidence: 63%
“…Potentially suitable clinical specimens for detection of chlamydial infection in women thus include urethral, vaginal, and endocervical swabs, self-inserted tampons, and FVU samples (3,12). For screening programs, noninvasive specimens, such as vaginal swabs, tampons, and FVU, are preferable to invasive urethral and endocervical swabs because they overcome several barriers associated with the traditional diagnostic pathway (5,11). Sensitivity of C. trachomatis detection with vaginal swabs has been shown to be similar to that with endocervical swabs or FVU samples (12,22,31).…”
mentioning
confidence: 95%
“…Previous reports indicate that self-sampling under optimal conditions in clinical or supervised settings is both accurate (8)(9)(10)(11)(12)(13)(14)(15) and preferred by patients (16)(17)(18)(19). In a recent systematic review, the sensitivity and specificity of self-sampling for identifying high-risk HPV were 74% and 88% compared with physician sampling (12).…”
Section: Introductionmentioning
confidence: 99%